Graphene‐Assisted Synthesis of 2D Polyglycerols as Innovative Platforms for Multivalent Virus Interactions. (26th March 2021) - Mohammadifar, Ehsan; Ahmadi, Vahid; Gholami, Mohammad Fardin; Oehrl, Alexander; Kolyvushko, Oleksandr; Nie, Chuanxiong; Donskyi, Ievgen S.; Herziger, Svenja; Radnik, Jörg; Ludwig, Kai; Böttcher, Christoph; Rabe, Jürgen P.; et al.
Abstract: 2D nanomaterials have garnered widespread attention in biomedicine and bioengineering due to their unique physicochemical properties. However, poor functionality, low solubility, intrinsic toxicity, and nonspecific interactions at biointerfaces have hampered their application in vivo. Here, biocompatible polyglycerol units are crosslinked in two dimensions using a graphene‐assisted strategy leading to highly functional and water‐soluble polyglycerols nanosheets with 263 ± 53 nm and 2.7 ± 0.2 nm average lateral size and thickness, respectively. A single‐layer hyperbranched polyglycerol containing azide functional groups is covalently conjugated to the surface of a functional graphene template through pH‐sensitive linkers. Then, lateral crosslinking of polyglycerol units is carried out by loading tripropargylamine on the surface of graphene followed by lifting off this reagent for an on‐face click reaction. Subsequently, the polyglycerol nanosheets are detached from the surface of graphene by slight acidification and centrifugation and is sulfated to mimic heparin sulfate proteoglycans. To highlight the impact of the two‐dimensionality of the synthesized polyglycerol sulfate nanosheets at nanobiointerfaces, their efficiency with respect to herpes simplex virus type 1 and severe acute respiratory syndrome corona virus 2 inhibition is compared to their 3D nanogel analogs. Four times stronger in virus inhibition suggests that 2D polyglycerols are superior to their current 3D counterparts. Abstract : A 2D hyperbranched polyglycerol and its sulfated counterpart are synthesized using a graphene‐assisted strategy. The synthesized 2D polymers are used to inhibit the infection by severe acute respiratory syndrome corona virus 2 and show an inhibitory concentration as low as 3 nm .